2014
DOI: 10.1007/s11517-014-1218-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alignment-free sequence representations on the semi-supervised classification of class C G protein-coupled receptors

Abstract: G protein-coupled receptors (GPCRs) are integral cell membrane proteins of relevance for pharmacology. The tertiary structure of the transmembrane domain, a gate to the study of protein functionality, is unknown for almost all members of class C GPCRs, which are the target of the current study. As a result, their investigation must often rely on alignments of their amino acid sequences. Sequence alignment entails the risk of missing relevant information. Various approaches have attempted to circumvent this ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…We assume that the majority of sequences are adequately characterized (that is, that they are correctly labeled in the database according to sub-family), but we are keen on investigating which sequences are commonly misclassified by computer-based methods and what type of misclassification they suffer. The starting point for these concerns are previously reported results indicating that the discriminatory classification of Class C GPCRs from transformations of their primary sequences shows clear limits [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the majority of sequences are adequately characterized (that is, that they are correctly labeled in the database according to sub-family), but we are keen on investigating which sequences are commonly misclassified by computer-based methods and what type of misclassification they suffer. The starting point for these concerns are previously reported results indicating that the discriminatory classification of Class C GPCRs from transformations of their primary sequences shows clear limits [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent analysis using semisupervised and supervised classification of class C GPCRs [8,9] with this type of transformation showed that overall accuracy (the ratio of correctly classified sequences) reaches an upper bound in the area of 90% that it is not significantly increased when more sophisticated physico-chemical transformations of the sequences are applied.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the same sequence dataset is visualized using a nonlinear dimensionality reduction (NLDR) technique, namely Generative Topographic Mapping (GTM [12]). This technique has been applied with success to many problems in biomedicine and bioinformatics [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This GPCR discrimination task has been addressed in the past using supervised [6], semi-supervised [7] and even fully unsupervised [8], [9] modelling approaches.…”
Section: Introductionmentioning
confidence: 99%